Factors facilitating and hindering the implementation of the European Society of Cardiology Syncope Guidelines at the Emergency Department: A nationwide qualitative study. (15th June 2021) - Ghariq, M.; van Bodegom-Vos, L.; Brignole, M.; Peeters, S.Y.G.; de Groot, B.; Kaal, E.C.A.; Hemels, M.E.W.; de Lange, F.J.; van Dijk, J.G.; Thijs, R.D.; ,
Abstract: Aims: Syncope care is often fragmented and inefficient. Structuring syncope care through implementation of guidelines and Syncope Units has been shown to improve diagnostic yield, reduce costs and improve quality of life. We implemented the European Society of Cardiology (ESC) 2018 syncope guidelines at the Emergency Departments (ED) and established Syncope Units in five Dutch hospitals. We evaluated the implementation process by identifying factors that hinder ('barriers') and facilitate ('facilitators') the implementation. Methods and results: We conducted, recorded and transcribed semi-structured interviews with 19 specialists and residents involved in syncope care from neurology, cardiology, internal medicine and emergency medicine. Two researchers independently classified the reported barriers and facilitators, according to the framework of qualitative research (Flottorp), which distinguished several separate fields ('levels'). Software package Atlas.ti was used for analysis. We identified 31 barriers and 22 facilitators. Most barriers occurred on the level of the individual health care professional (e.g. inexperienced residents having to work with the guideline at the ED) and the organizational context (e.g. specialists not relinquishing preceding procedures). Participants reported most facilitators at the level of innovation (e.g. structured work-flow at the ED). The multidisciplinary Syncope Unit was welcomed as useful solution to a perceived need in clinical practice. Conclusion: Implementing ESC syncope guidelines at the ED and establishing Syncope Units facilitated a structured multidisciplinary work-up for syncope patients. Most identified barriers related to the individual health care professional and the organizational context. Future implementation of the multidisciplinary guideline should be tailored to address these barriers. Highlights: We evaluated the implementation process of ESC syncope guidelines and identified 31 barriers and 22 facilitators. Most barriers concerned the individual health care professionaland the organizational context. Most facilitators were reported at the level of innovation. The multidisciplinary Syncope Unit was welcomed as useful solution to a perceived need in clinical practice. These barriers and facilitators should be used to designtailored interventions to impphese